ISLAMIC EDUCATION POLICY PROBLEMS IN INDONESIA - Ahmad Mohdlori; Muchammad Nuryadi; Nurjihadi . (TAWASUT, 2023)
AbstractIslamic education is a process of preparing one's future to reach maturitywhich is carried out by pious Muslim adults who deliver and guide their growthand development through Islamic teachings effectively and efficiently. Islamiceducation certainly provides guidance to a person towards his development inthe form of physical and spiritual in order to form a noble personality in himselfbased on Islamic norms. Islamic education in the education system is dividedinto three forms. First, Islamic education as an institution for its existence as anIslamic educational institution explicitly. Second, Islamic Education as aSubject there is religious education as one of the subjects that must be given atthe elementary level to college. Third, Islamic education as a value containsIslamic values in the education system. However, the problems in Islamiceducation, especially the policies implemented in educational institutions inIndonesia, are still very emerging from the past until now in the era ofglobalization and digitalization because it involves human resources which arealways dynamic in each era. Islamic education policies always try to beperfected and provide the best solutions for changes and improvements in theimplementation of Islamic education itself with evidence of revisions to laws orgovernment regulations on education that are always carried out.Keywords: Islamic Education, Problems and Policies